PERANCANGAN FASAD BANGUNAN PUSAT PERBELANJAAN MELALUI PENERAPAN TEMA METAFORA - jiffriandi 95 (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2018)
The city of Banda Aceh is a center for the development of sports activities in Aceh Province. In order to welcome the 2024 Aceh-North Sumatra PON in Banda Aceh as a sports development center in Aceh province must have facilities to sell sports equipment in one roof or centrally so as to facilitate consumers to get the desired sports products with a comfortable and safe feeling .shopping centers that will be designed must have the ability to attract consumers to continue to maintain their existence. In designing a shopping center, forms and facades have a very important role. The facade or visible part of a building is an element that cannot be removed from an architectural design product and is even the most important part of an architectural work, because it is this visible element that is first appreciated or seen. facade means a face of a building or the face or front of a building. Facades are a very important part of an architectural work, because these elements are parts that are always first appreciated by the public (connoisseurs of architectural works)We can enjoy the metaphor in architecture through an architectural thought process. Metaphors in architecture are built through the realization of design concepts. the concept is "moved" into three-dimensional space. Textures, shapes, colors designed to produce visual quality. The design of the facade must be able to express the identity of the function of the building itself which must be described from the shopping center. The facade in the building applies a secondary skin system. is a physical protector of buildings from exposure to weather such as rain and sunlight. As the name implies that is interpreted as a second skin, secondary skin is also able to reduce the heat of the sun while creating a shadow on the first skin.